The effects of misoprostol and famotidine on gastric injury caused by long term nonsteroid antiinflammatory drug usage - Yildiz, C.; Celiker, H.; Ayhan, S.; Bahcecioglu, I.H.; Karaoglu, A.; Kilicoglu, A.E. (Turkish Society of Gastroenterology, 1996)
To evaluate the effects of misoprostol and famotidine on gastric endoscopic scores and rheumatic symptoms during baseline, the first and the second months of the therapy, 32 cases taking long-term nonsteroid antiinflammatory drugs (NSAID) for their primary disease were divided randomly to two separate groups: group A (misoprostol) and group B (famotidine). 16 patients from group A and 16 patients from group B were administered 200 mcg misoprostol and 20 mg famotidine, respectively, per oral twice a day. All patients received 550 mg naproxen sodium per oral twice a day and 100 mg indomethacine suppository daily as NSAIDs. All the medications used were tolerated well during the study period. Significant decrease in endoscopic scores of group A compared with group B was observed despite NSAID administration (p<0.05). Rheumatic symptoms did not change with misoprostol and famotidine therapy (p>0.05).
UZUN DONEM NONSTEROID ANTIINFLAMATUAR ILAC KULLANIMINA BAGLI GASTRIK HASARDA MISOPROSTOL VE FAMOTIDIN'IN ETKILERI
Keywords: Endoscopy; Famotidine; Gastric injury; Misoprostol; NSAID